Rutin- potent natural thrombolytic agent - Dar, Mohammad Arif; Tabassum, Nahida (International Current Pharmaceutical Journal, 2012)
Thrombosis, the formation of blood clots, is a cause not only of heart attacks and strokes, but of deep venous thrombosis (DVT) and pulmonary embolism as well. The number one killer of Americans is a blood clot that blocks blood flow to the heart or to the brain and approximately half of all morbidity and mortality in the United States can be attributed to heart attack or stroke. All the blood clot related conditions are life-threatening, and so there is a need for safe, effective and preventive treatment. A natural substance rutin, also called rutoside, is a citrus flavonoid glycoside found in Fagopyrum esculentum (buckwheat), the leaves and petioles of Rheum species, and Asparagus. This flavonoid compound has shown effective thrombolytic activity (prevents the formation of blood clots) by blocking the enzyme protein disulfide isomerase (PDI) found in all cells involved in blood clotting. Food and Drug Administration (FDA) has established that rutin is safe and, thus provides a safe and inexpensive drug that could reduce recurrent clots and help save thousands of lives. DOI: http://dx.doi.org/10.3329/icpj.v1i12.12454 International Current Pharmaceutical Journal 2012, 1(12): 431-435